Project SEARCH UK – Evaluating Its Employment Outcomes. Issue 6 (2nd September 2015) - Kaehne, Axel
Abstract : Background: The study reports the findings of an evaluation of Project SEARCH UK. The programme develops internships for young people with intellectual disabilities who are about to leave school or college. The aim of the evaluation was to investigate at what rate Project SEARCH provided employment opportunities to participants. Methods: The evaluation obtained data from all sites operational in the UK at the time of evaluation ( n  = 17) and analysed employment outcomes. Results: Data were available for 315 young people ( n  = 315) in the programme and pay and other employment related data were available for a subsample. The results of the analysis suggest that Project SEARCH achieves on average employment rates of around 50 per cent. Conclusion: Project SEARCH UK represents a valuable addition to the supported employment provision in the UK. Its unique model should inform discussions around best practice in supported employment. Implications for other supported employment programmes are discussed.